Factors influencing health information system acceptance: a cross-sectional study from a low-middle-income country - Sawalha, Raya; Ahmad, Fayez; Al Zabadi, Hamzeh; Khayyat, Abdulsalam; Jallad, Samar Thabet; Amro, Tareq; Zagha, Rami (Frontiers in Health Services, 2024)
BackgroundThe Avicenna unified Health Information System (HIS) was implemented by the Palestinian Ministry of Health in 2010 across government hospitals. Despite its potential, the acceptance of Avicenna HIS by healthcare providers remains unclear after 14 years of application. Understanding the factors that influence healthcare provider acceptance is essential for optimizing the system's success. We investigated factors affecting acceptance of Avicenna HIS among healthcare providers in Palestinian healthcare institutions, focusing on perceived usefulness, ease of use, human factors, technological factors, and organizational support.Materials and methodsA cross-sectional study was conducted at the Palestine Medical Complex (PMC) in Ramallah, West Bank, where the Avicenna HIS has been fully implemented since 2010. A systematic random sampling was used to select participants, resulting in 300 completed questionnaires. The study utilized a self-administered questionnaire adapted from a structured tool based on the Technology Acceptance Model (TAM). The questionnaire was validated through expert review and pilot testing, achieving a Cronbach's alpha of 0.86. Each selected healthcare provider was contacted face-to-face, and written informed consent was obtained before administering the questionnaire.ResultsA total of 300 questionnaires were completed and returned. The study sample included 178 males (59.3%) and 122 females (40.7%). The majority of participants was aged 20–39 years (270 participants, 90%) and held a bachelor's degree (250 participants, 83.3%). Nurses comprised the largest professional group (153 participants, 51.0%). High levels of perceived usefulness and ease of use were reported, both with mean scores of 4.511 (S.D. = 0.295). Technological factors had a mean score of 4.004 (S.D. = 0.228), while organizational factors scored 2.858 (S.D. = 0.304). Overall acceptance of the HIS was moderately high, with a mean score of 4.218 (S.D. = 0.387). Significant differences in perceived usefulness and ease of use were noted based on gender, age, and experience.ConclusionThis study concludes that both technological and human factors significantly influence the acceptance of HIS among healthcare providers in Palestine. To improve HIS adoption, it is recommended to enhance system functionality, ensure reliable data quality, and provide comprehensive training programs for healthcare providers.